Correlation Between The Physical Activities and Physical Fitness Towards The Risk Musculoskeletal Disorder Of E-Sport Athletes - Almayda Putri, Salva (Proceeding of International Joint Conference on UNESA, 2025)
This study aims to determine the relationship between physical activity and physical fitness on the risk of musculoskeletal disorders in E-sport athletes PORDA Yogyakarta City. A quantitative research design with a correlational approach was used, with a population of 29 E-sport athletes who are members of the Yogyakarta City PORDA team. Data collection was carried out using validated instruments, such as the International Physical Activity Questionnaire (IPAQ), Nordic Body Map, and physical fitness tests such as the Back Strength Test, Hand Grip Test, and 12-minute Cooper test. The results showed that physical activity has a significant relationship with musculoskeletal disorder complaints in several parts of the athlete's body, with a Sig.<0.05 value and a negative correlation between -0.314 to -0.551. Physical fitness also had a significant association with musculoskeletal disorder (Sig.<0.05 and r 0.412-0.544). These findings indicate the importance of physical fitness in preventing musculoskeletal disorders and improving athlete performance. Further research is recommended to examine the effectiveness of physical training programs in reducing the risk of injury and improving the performance of E-sport athletes.